МИКАЭЛ ТАРИВЕРДИЕВ: ПЕТЬ, ЧТОБЫ СКАЗАТЬ - Матеосовна Азнаурян, Софа (Musical Armenia, 2011)
Composer, editor of "YSC Publishing House" of Yerevan Komitas named State Conservatory, Sofa M. Aznauryan writes the article "Mikael Tariverdiev, to sing for telling". The author writes about the interview with his wife Vera G. Tariverdieva taken on 5th of October 2010 after the concert in Aram Khachaturian's house museum. Before this one there were also concerts in Shoushi where the artists from Moscow had performed. The short playing by the composer sounded, vocal works with Japanese poets' and Bela Akhmadulina's poems (performed by Termine Yeghiazaryan-soprano, M. Tariverdiev fund's pension scholar), Trio "Opus post".